THE GEOCHEMICAL IMPLICATION OF A VARIABLE EU ANOMALY IN A FRACTURED GNEISS CORE: APPLICATION FOR UNDERSTANDING AM BEHAVIOR IN THE GEOLOGICAL ENVIRONMENT - Lee S.-G.; Kim Y.; Koh D.-C.; Chae B.-G.; Kim K.-H. (My University, 2004)
The rare earth elements (REEs) have been used as analogs for understanding the behavior of actinide elements in geological conditions. Here the authors discuss the usefulness of the change of Eu abundance in a fractured aquifer for deducing the behavior of Am under geological conditions. The REE abundance of fractured core samples from Precambrian crystalline rocks in the Namyangju area, Korea provides a good example of a water–rock interaction in the low temperature aqueous environment. The rock types studied are mainly biotite banded-gneisses with mineral assemblages dominated by biotite, K-feldspar, quartz and plagioclase. Calcite, chlorite, muscovite and sericite occur as secondary minerals, with calcite being the main filling material in fractures. In general, the core samples from 5 boreholes are enriched in light REE (LREE) and depleted in heavy REE (HREE), with (La/Yb)N=7.3 to 67.6 and have negative Eu anomalies. However, positive Eu anomalies also occur in the fractured core samples that contain secondary calcite. Results of leaching experiments show that a variation of chondrite-normalized REE patterns is associated with the fracture-filling calcite, where Eu has been reduced and selectively concentrated in the solutions from which calcite has precipitated. The cohesive energy of Am in actinide series is similar to that of Eu. Hence, the behavior of Eu in the fractured aquifer may be an important key to understanding and predicting the behavior of Am in the geological environment after radioactive waste disposal in the ground. In addition, a slight Yb anomaly from chondrite-normalized REE pattern can be observed by a calcite leaching test, which also suggests that extremely reducing conditions possibly existed in the...